Indonesia's Global Maritime Fulcrum Strategy: Navigating Great Power Competition and Regional Leadership in Indo-Pacific Security (2014-2024) - Elpeni Fitrah; Arief Bakhtiar Darmawan; Raden Mokhamad Luthfi (Andalas Journal of International Studies (AJIS), 2025)
This article analyzes Indonesia's Global Maritime Fulcrum (GMF) strategy from 2014 to 2024, tracing its transformation from a domestic development initiative to a refined diplomatic tool for managing great power rivalry in the Indo-Pacific. This research utilizes a qualitative case study technique with process tracing to examine official documents, diplomatic exchanges, and quantitative measurements, framed by middle power theory and maritime strategy concepts. The findings indicate that Indonesia's GMF strategy evolved through three distinct phases, achieving significant milestones such as a 234% enhancement in maritime surveillance coverage, the establishment of 89 bilateral maritime cooperation agreements, and effective mediation in regional maritime disputes with an 83% success rate. These results markedly surpassed earlier academic forecasts, demonstrating Indonesia's adept utilization of its geographic advantages and diplomatic skills to establish regional leadership despite the limitations of its middle power status. Despite the GMF's effectiveness being constrained by intensifying great power rivalry and internal limitations, Indonesia has adeptly established itself as a crucial player in Indo-Pacific maritime governance through the integration of institutional development, diplomatic efforts, and operational collaboration, providing significant insights into middle power conduct in intricate regional security contexts.